Software development in practice - Fishpool, Bernie; Fishpool, Mark (BCS, The Chartered Institute for IT, 2020)
Software development is becoming recognised more and more as an essential skill and profession in today's increasingly digital world. This book is a pragmatic guide to software development in practice. It explores the inner workings of software development in the context of the industry, covering good practice for software developers and providing you with tools and practical understanding you'll need to advance within the software development world.